Factors of Health Service Quality Dimensions Related to Patient Satisfaction - Sianturi, Laostiar; Ahmad Hafizullah Ritonga; Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The quality of healthcare services at Puskesmas Batang Beruh, Dairi Regency, is influenced by several dimensions of service quality, including Tangible (physical facilities), Reliability (reliability), Responsiveness (responsiveness), and Assurance (assurance). Each of these dimensions plays a crucial role in shaping patient satisfaction, which is a primary indicator of the service quality provided. Objective: This study aims to analyze the relationship between service quality dimensions (Tangible, Reliability, Responsiveness, Assurance) and patient satisfaction at Puskesmas Batang Beruh, Dairi Regency, in 2025. Method: This study employs a quantitative method with an analytical survey design. Data were collected through questionnaires distributed to patients at Puskesmas Batang Beruh, and the results were analyzed using logistic regression analysis to determine the factors influencing patient satisfaction. Results: The findings indicate that the Empathy and Reliability dimensions have a significant impact on patient satisfaction. Adequate physical facilities, timely service, and an empathetic relationship between nurses and patients contribute to increasing patient satisfaction levels. However, while Responsiveness is important, it is less influential than the other dimensions in affecting patient satisfaction. Conclusion: The Tangible (physical facilities), Reliability (reliability), and Empathy dimensions have the most significant impact on patient satisfaction at Puskesmas Batang Beruh. To improve patient satisfaction, it is essential for Puskesmas to continuously improve physical facilities, enhance service reliability, and foster empathetic attitudes among healthcare staff.